Early palliative care for solid and blood cancer patients and caregivers: Quantitative and qualitative results of a long-term experience as a case of value-based medicine - Bigi, Sarah; Borelli, Eleonora; Potenza, Leonardo; Gilioli, Fabio; Artioli, Fabrizio; Porzio, Giampiero; Luppi, Mario; Bandieri, Elena (Frontiers in Public Health, 2023)
Introduction Cancer patients and their caregivers have substantial unmet needs, that negatively impact the clinical outcome and quality of life. However, interventions aimed to address such needs are still suboptimal, failing to answer the recent healthcare call for the adoption of value-based models of care. In the case of incurable oncologic and hematologic cancers, a value-based model of care should plan advanced care on patients' needs and include the quality of death as an outcome. The integration of early palliative care into standard oncologic care for patients with advanced cancers represents a recent innovative model of assistance whose benefits for patients and caregivers are now widely recognized. The key elements underlying the reasons behind these benefits are the multidisciplinary collaboration (teamwork), an honest and empathetic communication between the early palliative care team, the patient, and the caregiver (rapport building), and the ability to detect changes in the physical/psychosocial wellbeing of the patient, along the whole disease trajectory (constant monitoring). Methods This community case study documents the quantitative and qualitative results of a long term clinical and research experience in delivering early palliative care service to address both solid and blood cancer patients' and their primary caregivers' needs. Results Data showed decreased use of chemotherapy, blood transfusions and referral to intensive care units near the end of life; increased life expectancy; improved symptom burden and mood; increased frequency of goals-of-care and advanced care planning conversations. Hope perception among bereaved caregivers was associated with resilience and realistic expectations raising from honest communication with the early palliative care team and appreciation toward the model. Patients and caregivers perceived the possibility of a good death as realistic and not as an unlikely event as it was for patients and caregivers on standard oncologic care only. Gratitude expressions toward the model and the team were frequently identified in their reports and positively associated with communication and spirituality. Conclusions These findings are discussed in the context of an updated literature review regarding value-based care and suggest that early palliative care integrated into standard oncology care may be considered as an effective model of value-based care.